2012
DOI: 10.1007/s00784-012-0803-4
|View full text |Cite
|
Sign up to set email alerts
|

Disk and joint morphology variations on coronal and sagittal MRI in temporomandibular joint disorders

Abstract: Our study highlights the existence of changes on coronal MRI in TMD patients which should be assessed for better understanding of the clinical evolution of temporomandibular disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 26 publications
1
27
0
6
Order By: Relevance
“…Regarding the coronal condylar angle, when comparing the means in the different positions of the disc, no statistical association was evident, like Almǎşan et al 50 However, it can be observed that in the coronal displacements, the coronal angle is smaller (rotated medially) than in the TMJ discs in normal position, as shown by Raustia et al 45 who found differences in this inclination between patients with temporomandibular dysfunction and the control group.…”
Section: Discussionmentioning
confidence: 87%
“…Regarding the coronal condylar angle, when comparing the means in the different positions of the disc, no statistical association was evident, like Almǎşan et al 50 However, it can be observed that in the coronal displacements, the coronal angle is smaller (rotated medially) than in the TMJ discs in normal position, as shown by Raustia et al 45 who found differences in this inclination between patients with temporomandibular dysfunction and the control group.…”
Section: Discussionmentioning
confidence: 87%
“…Temporomandibular joint dysfunction can be associated with malocclusion, false condyle position and condylar disk displacement [26,27]. To avert postoperative temporomandibular joint dysfunction, alterations in the condyle position or malocclusion should be avoided; this improves patients’ postoperative satisfaction and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed an association between disc displacement and changes in the morphology of the articular disc, in agreement with the literature. 7,15,24,[36][37][38] Most of the normally positioned discs showed a biconcave shape, while none of them had a folded shape. Additionally, all of the folded discs were found in patients in advanced stages of internal derangement (ADWOR).…”
mentioning
confidence: 99%